2013
DOI: 10.1038/nature12768
|View full text |Cite
|
Sign up to set email alerts
|

An Earth-sized planet with an Earth-like density

Abstract: Recent analyses 1-4 of data from the NASA Kepler spacecraft 5 have established that planets with radii within 25 per cent of Earth's (R⊕) are commonplace throughout the Galaxy, orbiting at least 16.5 per cent of Sun-like stars 1 . Because these studies were sensitive to the sizes of the planets but not their masses, the question remains whether these Earth-sized planets are indeed similar to the Earth in bulk composition. The smallest planets for which masses have been accurately determined 6,7 are Kepler-10b … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
163
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(164 citation statements)
references
References 27 publications
1
163
0
Order By: Relevance
“…Second and perhaps more importantly, the RV signal induced by stellar spots is expected to have an ≈λ −1 dependence for modest spot contrast temperatures, where λ is the wavelength (Reiners et al 2010;Anglada-Escudé et al 2012;Howard et al 2013;Pepe et al 2013;Marchwinski et al 2015;Plavchan et al 2015), which means that the effect of stellar spots on NIR RV measurements is less important than it is at visible wavelengths by a factor ∼4. However, there have also been predictions that the Zeeman effect resulting from the strong magnetic activity in young stars could cause jitter to increase as a function of wavelength (Reiners et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second and perhaps more importantly, the RV signal induced by stellar spots is expected to have an ≈λ −1 dependence for modest spot contrast temperatures, where λ is the wavelength (Reiners et al 2010;Anglada-Escudé et al 2012;Howard et al 2013;Pepe et al 2013;Marchwinski et al 2015;Plavchan et al 2015), which means that the effect of stellar spots on NIR RV measurements is less important than it is at visible wavelengths by a factor ∼4. However, there have also been predictions that the Zeeman effect resulting from the strong magnetic activity in young stars could cause jitter to increase as a function of wavelength (Reiners et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The method of Doppler radial velocity (RV) variations has proven itself fruitful in the last decades both for the identification of new exoplanets (e.g., Mayor & Queloz 1995;Marcy et al 1998Marcy et al , 2001Delfosse et al 1998a;Cochran et al 2002;Endl et al 2003;Butler et al 2004;Rivera et al 2005bRivera et al , 2010Meschiari et al 2011;Dumusque et al 2012;Montet et al 2014;Tuomi et al 2014) and for the confirmation of exoplanets detected by the method of transit (e.g., Kepler-78b; Akeson et al 2013;Pepe et al 2013;Sanchis-Ojeda et al 2013). Recent developments have shown that cool (3800 K) stellar hosts in the M spectral class represent valuable targets for the identification of new Earthmass planetary companions in the habitable zone using the RV method due to their smaller mass and significantly larger population (Henry et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this work we combine Kepler photometry with highprecision radial-velocity measurements of the Kepler-101 twoplanet system gathered in the context of the GTO program of the HARPS-N Consortium (Pepe et al 2013;Dumusque et al 2014). Kepler-101 was initially identified as Kepler object of interest 46 (KOI-46).…”
Section: Introductionmentioning
confidence: 99%
“…Only five other USPs have measured masses and densities: 55 Cnc (Fischer et al 2008;Dawson & Fabrycky 2010;Nelson et al 2014;Demory et al 2016), CoRoT-7b (Léger et al 2009;Bruntt et al 2010;Haywood et al 2014), Kepler-10b Esteves et al 2015), Kepler-78b (Howard et al 2013;Pepe et al 2013;Grunblatt et al 2015), and WASP-47e Dai et al 2015;Sinukoff et al 2017). These planets are plotted on the mass-radius diagram in Figure 7(b).…”
Section: Ultra-short-period Planetsmentioning
confidence: 99%